2012
DOI: 10.4236/psych.2012.35059
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Effects of Post-Learning Stress on Memory

Abstract: To investigate the enhancing effect of post-learning stress on memory, we requested 38 Japanese undergraduates to perform a learning task that involved positive, negative, and neutral words with controlled arousal and subsequently assigned them to a stress group (exposed to acute white noise) or a control group. After a 10-min filler task, we administered a delayed free recall test and a recognition test. We found that exposure to acute stress after learning significantly enhanced recognition memory of words, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Table 1 shows a representative listing of studies that (a) manipulated valence of words and (b) assessed memory using recognition. Although some studies that report signal detection-type measures did indeed find better recognition of negative words (e.g., Inaba et al, 2005; Kensinger & Corkin, 2003), others found the reverse (e.g., Lin & Tanno, 2012; Wang & Fu, 2011), and still others found no effect of valence (Gallant et al, 2018; Jermann et al, 2009).…”
mentioning
confidence: 97%
“…Table 1 shows a representative listing of studies that (a) manipulated valence of words and (b) assessed memory using recognition. Although some studies that report signal detection-type measures did indeed find better recognition of negative words (e.g., Inaba et al, 2005; Kensinger & Corkin, 2003), others found the reverse (e.g., Lin & Tanno, 2012; Wang & Fu, 2011), and still others found no effect of valence (Gallant et al, 2018; Jermann et al, 2009).…”
mentioning
confidence: 97%